The learning medium design of language intelligence for elementary student based on used oil bottle upcycling - Sulistyo Setiawan; Dedy Ismail (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
Language is an essential factor that distinguishes humans from animals. With human language, humans are able to communicate their thoughts and feelings both orally and in writing. The development of communicating with this language occurs both in the home environment, school, and the wider community. When these environments do not pay enough attention to developing language skills or what Gardner calls Language Intelligence, then this intelligence does not develop optimally. Based on preliminary studies in elementary school, many students whose language intelligence is not developing optimally The lack of development of Language Intelligence is partly due to the lack of media that can develop it. Departing from this, the research using the Stanford University Design Thinking research method aims to produce learning media to develop language intelligence using used oil bottles designed with the principle of upcycling.